2014
DOI: 10.3201/eid2007.131396
|View full text |Cite
|
Sign up to set email alerts
|

Neisseria gonorrhoeaeStrain with Reduced Susceptibilities to Extended-Spectrum Cephalosporins

Abstract: The spread of Neisseria gonorrhoeae strains with reduced susceptibility to extended-spectrum cephalosporins is an increasing public health threat. Using Etest and multiantigen sequence typing, we detected sequence type 1407, which is associated with reduced susceptibilities to extended-spectrum cephalosporins, in 4 major populated regions in California, USA, in 2012.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 14 publications
(17 reference statements)
0
11
0
2
Order By: Relevance
“…gonorrhoeae was a major cause for concern in the US and abroad, and a recent study has described cephalosporin-resistant N . gonorrhoeae in the United States [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…gonorrhoeae was a major cause for concern in the US and abroad, and a recent study has described cephalosporin-resistant N . gonorrhoeae in the United States [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Asymptomatic infection in women can be concerning, since these women do not seek treatment, which results in untreated gonococcal infection that can lead to several serious complications, including infertility and ectopic pregnancy (5,6) as well as the possibility of further spreading the disease, a public health concern. While the majority of gonococcal infections are easily treated with antibiotic intervention, strains of N. gonorrhoeae resistant to several of the antibiotics commonly used to treat this infection have begun to emerge worldwide (7)(8)(9)(10)(11). N. gonorrhoeae remains a significant STI worldwide, and new strategies are needed to combat this infection.…”
mentioning
confidence: 99%
“…In addition to the prediction of ciprofloxacin susceptibility, our real-time PCR method could potentially be adapted to detect other mutations that may confer antimicrobial resistance. A recent study reported the presence of mosaic penA allele XXXIV in all N. gonorrhoeae isolates from major population centers in California with elevated MICs to ceftriaxone or cefixime (19), suggesting that this mosaic allele could serve as an appropriate target for prediction of increased extended-spectrum cephalosporin MICs in our local population. We found that the gyrA RT-PCR fit well into our current molecular diagnostic workflow; in particular, the use of remnant DNA extracted from the Cobas 4800 system allows a shorter turnaround time for producing gyrA genotype results-an approach demonstrated by others, in a recent report (20).…”
mentioning
confidence: 77%